Water removal in MR spectroscopic imaging with Casorati singular value decomposition - Shamaei, Amirmohammad; Starcukova, Jana; Rizzo, Rudy; Starcuk, Zenon (Magnetic resonance in medicine, 2024)
PURPOSE: Water removal is one of the computational bottlenecks in the processing of high-resolution MRSI data. The purpose of this work is to propose an approach to reduce the computing time required for water removal in large MRS data. METHODS: In this work, we describe a singular value decomposition-based approach that uses the partial position-time separability and the time-domain linear predictability of MRSI data to reduce the computational time required for water removal. Our approach arranges MRS signals in a Casorati matrix form, applies low-rank approximations utilizing singular value decomposition, removes residual water from the most prominent left-singular vectors, and finally reconstructs the water-free matrix using the processed left-singular vectors. RESULTS: We have demonstrated the effectiveness of our proposed algorithm for water removal using both simulated and in vivo data. The proposed algorithm encompasses a pip-installable tool ( https://pypi.org/project/CSVD/), available on GitHub ( https://github.com/amirshamaei/CSVD), empowering researchers to use it in future studies. Additionally, to further promote transparency and reproducibility, we provide comprehensive code for result replication. CONCLUSIONS: The findings of this study suggest that the proposed method is a promising alternative to existing water removal methods due to its low processing time and good performance in removing water signals.
Keywords: algoritmy; Reproducibility of Results; voda; Magnetic Resonance Imaging; low-rank approximations; water removal; magnetická rezonanční spektroskopie; reprodukovatelnost výsledků; Water; Magnetic Resonance Spectroscopy; MR spectroscopic imaging; magnetická rezonanční tomografie; functional MRS; water suppression; Algorithms